Full response prediction for locally modified mechanical systems using the concept of equivalent additional force. (4th August 2020) - Liao, Xuhui; Li, Shunming; Xu, Yong; Meng, Haodong; Zhao, Jingbo
Abstract: Evaluating the dynamic properties of structures subjected to local modifications is an important issue in the field of structural dynamics. Most studies are focused on estimating the eigenvalues and eigenvectors of modified structures. However, in many cases, evaluating the responses of the modified structure is more direct and useful for the analysis. A general method for predicting the full responses of locally modified structures is proposed in this paper. The concept of equivalent additional force (EAF) is suggested to address this issue in a general framework. Seven typical cases of modifications and the case of multiple modifications are investigated in detail. In this method, the EAFs are expressed by the unknown responses of the modified structures and then the unknown responses can be easily calculated based on the responses of the original structure. The novelty of this paper is that any structural modification can be regarded as some EAFs applied to the original structure, which not only simplifies the response prediction for modified structures but also provides a new perspective for comprehending the problem of structural modification. The proposed method is illustrated by a numerical example and validated using data generated by finite element (FE) simulations. Highlights: A novel method for predicting the responses of modified structures is proposed. The equivalent mechanical models for typical structural modifications are given. Structural modifications are investigated in a unified framework. Transmissibility matrices are utilized to simplify the response prediction.